Factors influencing the formation of business ventures - Abdul Majid, Izaidin; Dora, Mohd Taib; Kamarudin, Mohd Fauzi (Penerbit Universiti Teknikal Malaysia Melaka, 2008)
The reasons for new firm starts are complex and a combination of factors will often contribute to venture creation. This research explores the prevalence of entrepreneurial activities, which is measured in terms of the involvement in business activities amongst a relatively huge number of respondents. Factors such as feeling contented with the currently acquired income, preferring salaried job rather than doing business, no interest in establishing own business and do not know of how to get access to capital are among the various factors that were identified as common barriers to starting-up own businesses. Some patterns of relationship between the related demographic variables and the propensity to entrepreneurial and business activities were also explored in this research with the intention to uncover some general picture of the Malaysian business context.